Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance?. (10th October 2018) - Wang, Zhi; Reimsbach, Daniel; Braam, Geert
Abstract: This study examines whether and how political embeddedness influences the diffusion of corporate social responsibility (CSR) practices in China. Specifically, we investigate how government ownership and political connections affect Chinese listed firms' likelihood of issuing CSR reports, as well as the underlying CSR performance (CSRP) and its relation to corporate financial performance (CFP). Using panel data from 15, 419 publicly traded firm-year observations in China for the years 2008–2014, the results show that politically embedded firms, and in particular firms that are centrally politically embedded, are more likely to issue CSR reports than firms without political embeddedness. The results also indicate that politically embedded firms, on average, have a higher CSRP than non-politically embedded firms. In addition, we find that for politically embedded firms, CSRP is more negatively related to financial performance than for firms without political embeddedness. This indicates that political embeddedness also affects the trade-off between CFP and CSRP. Our research, thus, provides evidence not only of the effectiveness of government-induced CSR policies but also of their efficiency, i.e., the potential opportunity costs that the policies imply. Furthermore, our results show that different types and levels of political embeddedness play considerable but different roles in explaining firms' CSR-related practices.